The Development of Arthropod Segmentation Across the Embryonic/Post-embryonic Divide – An Evolutionary Perspective - Fusco, Giuseppe; Minelli, Alessandro (Frontiers in Ecology and Evolution, 2021)
In many arthropods, the appearance of new segments and their differentiation are not completed by the end of embryogenesis but continue, in different form and degree, well after hatching, in some cases up to the last postembryonic molt. Focusing on the segmentation process currently described as postembryonic segment addition (or, anamorphosis), we revise here the current knowledge and discuss it in an evolutionary framework which involves data from fossils, comparative morphology of extant taxa and gene expression. We advise that for a better understanding of the developmental changes underlying the evolution of arthropod segmentation, some key concepts should be applied in a critical way. These include the notion of the segment as a body block and the idea that hatching represents a well-defined divide, shared by all arthropods, between two contrasting developmental phases, embryonic vs. postembryonic. This eventually reveals the complexity of the developmental processes occurring across hatching, which can evolve in different directions and with a different pace, creating the observed vagueness of the embryonic/postembryonic divide.